Counseling Deficiency of Mental Health Care among Adolescent In The 'PKPR' Program - Mohammad Saljan; Syaifoel Hardy (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The increasing number of adolescent health issues are mostly related to early marriage, reproductive health, sexually transmitted diseases (HIV/AIDS) and drug abuse. We chose the topic because of lacking mental health consulting services aspect in the health care services for adolescent health care (PKPR) program by the Puskesmas and offering solutions is of important. This study used a qualitative method with a descriptive design. The research respondents were four from East Java, Aceh, Central Sulawesi and Sumbawa. The inclusion criteria were healthy Indonesian citizens and had heard of the term PKPR. The exclusion criteria were non-Indonesian citizens, sick people (physically or mentally) and had never heard of the term PKPR. The instrument was a semi-structured question. The data was analyzed by Thematic Analysis supported by Appreciative Inquiry (AI). We found the ineffectiveness of mental health services of PKPR program for adolescents. Three issues that need to be underlined were the deficiency of mental health services by the healthcare profession, the lack of adequate service center infrastructure and the need for youth training. Our recommendation was mental health consulting services should be the core need in the PKPR services. Abstrak: Meningkatnya jumlah masalah kesehatan di kalangan remaja sebagian besar terkait dengan pernikahan dini, kesehatan reproduksi, penyakit menular seksual (HIV/AIDS) dan penyalahgunaan narkoba. Kami pilih topic ini karena untuk mengkaji aspek pelayanan konsultasi kesehatan jiwa dalam pelayanan kesehatan untuk program perawatan kesehatan remaja (PKPR) oleh Puskesmas dan menawarkan solusi. Penelitian ini menggunakan metode kualitatif dengan desain deskriptif. Responden penelitian berjumlah 4 orang yang berasal dari Jawa Timur, Aceh, Sulawesi Tengah dan Sumbawa. Kriteria inklusi adalah warga negara Indonesia yang sehat dan pernah mendengar istilah PKPR. Kriteria eksklusi adalah bukan WNI, orang sakit (fisik atau mental) dan belum pernah mendengar istilah PKPR. Instrumen yang digunakan adalah pertanyaan semi terstruktur. Data dianalisis dengan Analisis Tematik yang didukung oleh Appreciative Inquiry (AI). Kami menemukan ketidakefektifan pelayanan kesehatan jiwa program PKPR bagi remaja. Tiga isu yang perlu digarisbawahi adalah kurangnya layanan kesehatan jiwa oleh profesi kesehatan, kurangnya infrastruktur pusat layanan yang memadai dan perlunya pelatihan bagi kaum muda. Rekomendasi kami adalah layanan konsultasi kesehatan jiwa harus menjadi kebutuhan inti dalam layanan PKPR.